MOF-loaded red phosphorus lithium ion capacitor negative electrode material, preparation method thereof and lithium ion capacitor
By using the MOF-loaded red phosphorus method in lithium-ion capacitors, the problems of poor conductivity and volume expansion of red phosphorus are solved, and high reversible specific capacity and excellent cycling stability are achieved.
Patent Information
- Application Number
- CN202510079047.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-11
AI Technical Summary
As the negative electrode material of lithium-ion capacitors, red phosphorus has poor conductivity and volume expansion problems during cyclic charging and discharge limits its electrochemical performance and cyclic stability.
The method of loading red phosphorus by MOF (metal organic frame material) is adopted to provide a load space for red phosphorus through the high porosity and large specific surface area of MOF, buffering the volume changes of red phosphorus during the deintercalation of lithium ions, and improving the specific surface area and stability of MOF through carbonization treatment.
The cyclic stability and reversible specific capacity of red phosphorus as a negative electrode material are significantly improved, and the overall performance of lithium-ion capacitors is improved.
Smart Images

Figure CN119811902A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage, and provides a MOF-loaded red phosphorus lithium ion capacitor negative electrode material, a preparation method thereof, and a lithium ion capacitor. Background Art
[0002] As a new type of energy storage device, lithium-ion capacitors are widely used in power generation, transportation and other fields due to their high power density and ultra-long cycle life. Lithium-ion capacitors are generally composed of lithium-ion battery negative electrodes, supercapacitor positive electrodes and lithium salt electrolytes. They have both high energy density and high power density and are considered to be a very promising energy storage device.
[0003] The negative electrode of lithium-ion capacitors is generally divided into three types according to the energy storage mechanism: embedded type, conversion type, and alloy type. Red phosphorus based on the alloy reaction mechanism is a very promising negative electrode material. It has an ultra-high theoretical specific capacity (2596mA·h·g -1 ), which has great application prospects for obtaining high energy density energy storage devices. However, poor conductivity and volume expansion during cyclic charge and discharge restrict the electrochemical performance of red phosphorus, limiting the further development of red phosphorus as a negative electrode. Summary of the invention
[0004] In order to solve the above problems and obtain a lithium ion capacitor red phosphorus negative electrode with ultra-long cycle life and high specific capacity, the present application provides a MOF-loaded red phosphorus lithium ion capacitor negative electrode material. The negative electrode material has high reversible specific capacity and excellent cycle stability, which is conducive to improving the potential of red phosphorus in practical applications.
[0005] The present invention also provides a method for preparing the MOF-loaded red phosphorus lithium ion capacitor negative electrode material.
[0006] The invention also provides a lithium ion capacitor.
[0007] The present invention adopts the following technical solutions:
[0008] A MOF (metal organic framework) loaded red phosphorus lithium ion capacitor negative electrode material comprises MOF and red phosphorus loaded in the pores of the MOF; wherein the loading rate of the red phosphorus on the MOF is 15-25%.
[0009] Preferably, the MOF precursor is micrometer- or nanometer-sized cubic particles.
[0010] By adopting the above technical solution, MOF precursor is used as a carrier, which has the structural advantages of high porosity and large specific surface area; it provides abundant loading space for red phosphorus, can effectively buffer the volume change of red phosphorus during the process of lithium ion insertion and extraction, and significantly improves the cycle stability of red phosphorus as a negative electrode material.
[0011] By selecting different ligands and metal salts to synthesize MOF, the specific surface area of MOF can be increased, and micropores, mesopores and macropores with different proportions can be obtained.
[0012] Preferably, the red phosphorus is loaded onto the MOF precursor by evaporation-deposition method.
[0013] By adopting the above technical solution, red phosphorus is nanosized and adsorbed and confined in the pores of the MOF precursor, thereby achieving effective loading of red phosphorus by MOF and improving the overall conductivity of the electrode negative material, which is conducive to giving full play to the advantage of the ultra-high theoretical specific capacity of the red phosphorus negative electrode and achieving high reversible specific capacity and excellent long-cycle stability.
[0014] The present application also provides a method for preparing a negative electrode material of a MOF-loaded red phosphorus lithium ion capacitor, which adopts the following technical solution:
[0015] A method for preparing a negative electrode material of a MOF-loaded red phosphorus lithium ion capacitor comprises the following steps:
[0016] (1) Mix MOF and red phosphorus and place them in a sealed container;
[0017] (2) The sealed container is heated and heat treated in a vacuum or inert gas state, and then cooled to obtain the MOF-loaded red phosphorus lithium ion capacitor negative electrode material. The cooling in the present invention is natural cooling.
[0018] By adopting the above technical scheme, carbonization and loading of red phosphorus are carried out simultaneously under vacuum or inert gas conditions. On the one hand, carbonization of MOF precursor can improve its specific surface area and framework stability. On the other hand, by loading red phosphorus simultaneously, the carbon atoms on the MOF precursor can interact with P to form PC bonds, which is beneficial to limit the volume expansion of red phosphorus and improve life stability. At the same time, the one-step carbonization-loading step simplifies the process, is beneficial to improve preparation efficiency, and reduces problems such as excessive errors and product contamination caused by multiple process steps.
[0019] Loading red phosphorus onto a carbon matrix (obtained by carbonization of MOF precursor) improves the conductivity of the red phosphorus-carbon battery negative electrode material, which can give full play to the advantages of the ultra-high theoretical specific capacity of the red phosphorus negative electrode, making the red phosphorus-carbon battery negative electrode material have excellent reversible specific capacity; the porous high specific surface area MOF can effectively buffer the volume change of red phosphorus during the lithium ion insertion and extraction process of charging and discharging, making the red phosphorus-carbon battery negative electrode material have excellent cycle stability.
[0020] Preferably, the heat treatment process is to heat up to 600-800℃ at a rate of 3-5℃ / min for heat treatment (carbonization, loading treatment), keep warm for 2-5h, and then cool down naturally to room temperature. By adopting the above technical solution, heating makes the red phosphorus evaporate, and then slowly cools down to allow the red phosphorus vapor to fully enter and deposit in the pores of MOF. The particle size of the red phosphorus particles depends on the pore size, thus achieving the nano-size of the red phosphorus and making the porous carbon carrier effectively load the nano red phosphorus.
[0021] Preferably, the heat treatment is specifically as follows: heating to 700°C at a rate of 3-5°C / min, then cooling to 300°C at a rate of 2-5°C / min, and keeping the temperature for 10-14 hours; then cooling naturally to room temperature. After heating, the temperature is uniformly lowered to about 300°C and then kept warm, which can fully convert white phosphorus into red phosphorus and increase the yield of red phosphorus.
[0022] Preferably, in the vacuum or inert gas atmosphere, the inert gas is argon. Under high temperature conditions, the presence of argon will cause a certain air pressure in the closed container, making it difficult for red phosphorus to diffuse to the container wall, ensuring that red phosphorus can be fully deposited in the pores of the MOF precursor, so that MOF can effectively buffer the volume change of red phosphorus during the charge and discharge process; when the air pressure is reduced, even in a vacuum state, red phosphorus is easy to diffuse to the container wall, resulting in a large amount of loss, so that the red phosphorus loaded on the MOF is small, reducing the material specific capacity. Preferably, the argon atmosphere is 0.5~1 atmospheres.
[0023] Preferably, the mass ratio of the MOF precursor to red phosphorus is (1-3): 1. By limiting the mass ratio of the MOF precursor to red phosphorus, it is possible to ensure that the red phosphorus is effectively deposited in the pores of the MOF precursor, give full play to the buffering effect of the MOF precursor on the volume change of red phosphorus, reduce the possibility of red phosphorus being deposited on the surface of the MOF precursor due to excessive red phosphorus loading, and then falling off from the carbon matrix during the charge and discharge process, thereby ensuring that the red phosphorus-carbon battery negative electrode material has better cycle stability; at the same time, it can reduce the possibility of insufficient specific capacity of the red phosphorus-carbon battery negative electrode material due to too low red phosphorus loading.
[0024] Preferably, the mass ratio of the MOF precursor to red phosphorus is (1-3):1.
[0025] By adopting the above technical solution, the MOF precursor can effectively load red phosphorus and effectively buffer the volume change of red phosphorus during the lithium ion insertion and extraction process, so that the red phosphorus-carbon battery negative electrode material has a high reversible specific capacity and excellent cycle stability.
[0026] Wherein, the MOF precursor is prepared by the following steps:
[0027] Add the organic ligand to 20-100 ml of methanol to disperse it in the methanol;
[0028] Add the hydrated metal salt to 20-100 ml of methanol to disperse it in the methanol;
[0029] The two solutions are mixed, heated to 100-150°C, and stirred for 24-48 hours to allow for a full reaction;
[0030] The obtained solution is centrifuged, washed, and vacuum dried to obtain a MOF precursor. Specifically, the obtained solution is light yellow, the obtained solution is centrifuged, repeatedly washed with ethanol or methanol for 3-5 times, and finally placed in a vacuum drying oven at 70-80°C for 10-12 hours to obtain a MOF precursor.
[0031] The MOF in the present invention is obtained by a solvent thermal method using dimethylimidazole or terephthalic acid as an organic ligand and a hydrated metal salt as a metal center.
[0032] Wherein, the organic ligand is one of dimethylimidazole and terephthalic acid; the hydrated metal salt is one of zinc nitrate hexahydrate and zinc acetate.
[0033] Wherein, the mass ratio of the organic ligand to the hydrated metal salt is 1:(2-3).
[0034] In summary, this application has the following beneficial effects:
[0035] 1. This application uses MOF precursor as a carbon source, giving full play to the advantages of MOF precursor with multi-level pores and large specific surface area, and obtains high-performance MOF-loaded red phosphorus lithium ion capacitor negative electrode materials, which is helpful to promote the rapid development of red phosphorus in lithium ion capacitors;
[0036] 2. This application designs and constructs a multi-level porous carbon framework structure, which is used as a carbon matrix to achieve effective loading of nano red phosphorus. The synergistic effect of nano-sized and multi-level porous carbon framework structures is conducive to giving full play to the advantages of the ultra-high theoretical specific capacity of the red phosphorus negative electrode, so that the MOF-loaded red phosphorus lithium ion capacitor negative electrode material has a high reversible specific capacity and excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a SEM image of the MOF-loaded red phosphorus lithium ion capacitor negative electrode material prepared in Example 1;
[0038] Figure 2 This is a SEM image of the MOF-supported red phosphorus lithium ion capacitor negative electrode material prepared in Example 3;
[0039] Figures 3 to 8 are electrochemical test diagrams of Examples 1 to 8;
[0040] Fig. 9 This is a graph of the rate test results of Example 12. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0042] The present application is further described in detail below with reference to the accompanying drawings and embodiments.
[0043] Example 1
[0044] A MOF-loaded red phosphorus lithium ion capacitor negative electrode material is prepared by the following steps:
[0045] Dimethylimidazole and zinc acetate hexahydrate were dissolved in 50 ml of methanol solution in a mass ratio of 1:2, and then the two solutions were mixed, heated and stirred at 100°C for 24 hours, and then centrifuged and dried overnight to obtain a MOF precursor.
[0046] The MOF precursor and red phosphorus were simply mixed in a mass ratio of 1:1, placed in a closed container, and calcined under vacuum at a calcination temperature of 700°C, a heating rate of 5°C / min, and a holding time of 3h. The temperature was then lowered to 300°C at a rate of 5°C / min, and the mixture was kept warm for 12h. Finally, the mixture was naturally cooled to obtain a MOF-loaded red phosphorus lithium ion capacitor negative electrode material.
[0047] Example 2
[0048] A MOF-loaded red phosphorus lithium ion capacitor negative electrode material is prepared by the following steps:
[0049] Terephthalic acid and zinc acetate hexahydrate were dissolved in 50 ml of methanol solution in a mass ratio of 1:2, and then the two solutions were mixed, heated and stirred at 100°C for 24 hours, and then centrifuged and dried overnight to obtain a MOF precursor.
[0050] The MOF precursor and red phosphorus were simply mixed in a mass ratio of 1:1, placed in a closed container, and calcined under argon (1 atmosphere) at a calcination temperature of 600°C, a heating rate of 5°C / min, and a holding time of 3h. The temperature was then lowered at a rate of 2°C / min to 300°C, kept for 12h, and finally cooled naturally to prepare a MOF-loaded red phosphorus lithium ion capacitor negative electrode material.
[0051] Example 3
[0052] A MOF-loaded red phosphorus lithium ion capacitor negative electrode material is prepared by the following steps:
[0053] Terephthalic acid and zinc acetate hexahydrate were dissolved in 50 ml of methanol solution in a mass ratio of 1:2, and then the two solutions were mixed, heated and stirred at 100°C for 24 hours, and then centrifuged and dried overnight to obtain a MOF precursor.
[0054] The MOF precursor and red phosphorus were simply mixed in a mass ratio of 1:1, placed in a closed container, and calcined under an argon atmosphere (1 atmosphere) at a calcination temperature of 700°C, a heating rate of 5°C / min, and a holding time of 3h. The temperature was then lowered at a rate of 2°C / min to 300°C, kept for 12h, and finally naturally cooled to prepare a MOF-loaded red phosphorus lithium ion capacitor negative electrode material.
[0055] Example 4
[0056] A MOF-loaded red phosphorus lithium ion capacitor negative electrode material is prepared by the following steps:
[0057] Terephthalic acid and zinc acetate hexahydrate were dissolved in 50 ml of methanol solution in a mass ratio of 1:2, and then the two solutions were mixed, heated and stirred at 100°C for 24 hours, and then centrifuged and dried overnight to obtain a MOF precursor.
[0058] The MOF precursor and red phosphorus were simply mixed in a mass ratio of 1:1, placed in a closed container, and calcined under an argon atmosphere (1 atmosphere) at a calcination temperature of 800°C, a heating rate of 5°C / min, and a holding time of 3h. The temperature was then lowered at a rate of 2°C / min to 300°C, kept for 12h, and finally naturally cooled to prepare a MOF-loaded red phosphorus lithium ion capacitor negative electrode material.
[0059] Example 5
[0060] A MOF-loaded red phosphorus lithium ion capacitor negative electrode material is prepared by the following steps:
[0061] Terephthalic acid and zinc acetate hexahydrate were dissolved in 50 ml of methanol solution in a mass ratio of 1:2, and then the two solutions were mixed, heated and stirred at 100°C for 24 hours, and then centrifuged and dried overnight to obtain a MOF precursor.
[0062] The MOF precursor and red phosphorus were simply mixed in a mass ratio of 1:1, placed in a closed container, and calcined under an argon atmosphere (0.5 atmospheres) at a calcination temperature of 700°C, a heating rate of 5°C / min, and a holding time of 3h. The temperature was then lowered at a rate of 2°C / min to 300°C, kept for 12h, and finally naturally cooled to prepare a MOF-loaded red phosphorus lithium ion capacitor negative electrode material.
[0063] Example 6
[0064] A MOF-loaded red phosphorus lithium ion capacitor negative electrode material is prepared by the following steps:
[0065] Terephthalic acid and zinc acetate hexahydrate were dissolved in 50 ml of methanol solution in a mass ratio of 1:2, and then the two solutions were mixed, heated and stirred at 100°C for 24 hours, and then centrifuged and dried overnight to obtain a MOF precursor.
[0066] The MOF precursor and red phosphorus were simply mixed in a mass ratio of 1:1, placed in a closed container, and calcined under vacuum at a calcination temperature of 700°C, a heating rate of 5°C / min, and a holding time of 2h. The temperature was then lowered at a rate of 3°C / min to 300°C, kept for 10h, and finally cooled naturally to prepare a MOF-loaded red phosphorus lithium ion capacitor negative electrode material.
[0067] Example 7
[0068] A MOF-loaded red phosphorus lithium ion capacitor negative electrode material is prepared by the following steps:
[0069] Terephthalic acid and zinc acetate hexahydrate were dissolved in 50 ml of methanol solution in a mass ratio of 1:2, and then the two solutions were mixed, heated and stirred at 100°C for 24 hours, and then centrifuged and dried overnight to obtain a MOF precursor.
[0070] The MOF precursor and red phosphorus were simply mixed in a mass ratio of 2:1, placed in a closed container, and calcined under an argon atmosphere (1 atmosphere) at a calcination temperature of 700°C, a heating rate of 5°C / min, and a holding time of 3h. The temperature was then cooled at a rate of 2°C / min to 300°C, kept for 12h, and finally naturally cooled to prepare a MOF-loaded red phosphorus lithium ion capacitor negative electrode material.
[0071] Example 8
[0072] A MOF-loaded red phosphorus lithium ion capacitor negative electrode material is prepared by the following steps:
[0073] Terephthalic acid and zinc acetate hexahydrate were dissolved in 50 ml of methanol solution in a mass ratio of 1:2, and then the two solutions were mixed, heated and stirred at 100°C for 24 hours, and then centrifuged and dried overnight to obtain a MOF precursor.
[0074] The MOF precursor and red phosphorus were simply mixed in a mass ratio of 3:1, placed in a closed container, and calcined under an argon atmosphere (1 atmosphere) at a calcination temperature of 700°C, a heating rate of 5°C / min, and a holding time of 3h. The temperature was then lowered to 300°C at a rate of 2°C / min, kept for 12h, and finally naturally cooled to prepare a MOF-loaded red phosphorus lithium ion capacitor negative electrode material.
[0075] Example 9
[0076] A MOF-loaded red phosphorus lithium ion capacitor negative electrode material is prepared by the following steps:
[0077] Terephthalic acid and zinc acetate hexahydrate were dissolved in 100 ml of methanol solution in a mass ratio of 1:2, and then the two solutions were mixed, heated and stirred at 100°C for 36 hours, and then centrifuged and dried overnight to obtain a MOF precursor.
[0078] The MOF precursor and red phosphorus were simply mixed in a mass ratio of 1:1, placed in a closed container, and calcined under an argon atmosphere (1 atmosphere) at a calcination temperature of 700°C, a heating rate of 3°C / min, and a holding time of 5h. The temperature was then lowered to 300°C at a rate of 5°C / min, kept for 14h, and finally naturally cooled to prepare a MOF-loaded red phosphorus lithium ion capacitor negative electrode material.
[0079] Example 10
[0080] A MOF-loaded red phosphorus lithium ion capacitor negative electrode material is prepared by the following steps:
[0081] Terephthalic acid and zinc acetate hexahydrate were dissolved in 20 ml of methanol solution in a mass ratio of 1:2, and then the two solutions were mixed, heated and stirred at 150° C. for 24 hours, and then centrifuged and dried overnight to obtain a MOF precursor.
[0082] The MOF precursor and red phosphorus were simply mixed in a mass ratio of 1:1, placed in a closed container, and calcined under an argon atmosphere (1 atmosphere) at a calcination temperature of 700°C, a heating rate of 3°C / min, and a holding time of 3h. The temperature was then lowered to 300°C at a rate of 3°C / min, kept for 12h, and finally cooled naturally to prepare a MOF-loaded red phosphorus lithium ion capacitor negative electrode material.
[0083] Embodiment 11
[0084] A MOF-loaded red phosphorus lithium ion capacitor negative electrode material is prepared by the following steps:
[0085] Terephthalic acid and zinc acetate hexahydrate were dissolved in 50 ml of methanol solution in a mass ratio of 1:3, and then the two solutions were mixed, heated and stirred at 100° C. for 48 hours, and then centrifuged and dried overnight to obtain a MOF precursor.
[0086] The MOF precursor and red phosphorus were simply mixed in a mass ratio of 1:1, placed in a closed container, and calcined under an argon atmosphere (1 atmosphere) at a calcination temperature of 700°C, a heating rate of 5°C / min, and a holding time of 3h. The temperature was then lowered at a rate of 2°C / min to 300°C, kept for 12h, and finally naturally cooled to prepare a MOF-loaded red phosphorus lithium ion capacitor negative electrode material.
[0087] Example 12
[0088] A MOF-loaded red phosphorus lithium ion capacitor negative electrode material is prepared by the following steps:
[0089] Terephthalic acid and zinc nitrate hexahydrate were dissolved in 50 ml of methanol solution in a mass ratio of 1:2, and then the two solutions were mixed, heated and stirred at 100°C for 24 hours, and then centrifuged and dried overnight to obtain a MOF precursor.
[0090] The MOF precursor and red phosphorus were simply mixed in a mass ratio of 1:1, placed in a closed container, and calcined in an argon atmosphere (1 atmosphere) at a calcination temperature of 400°C, a heating rate of 5°C / min, and a holding time of 3h. Finally, the mixture was naturally cooled to prepare a MOF-loaded red phosphorus lithium ion capacitor negative electrode material.
[0091] Performance testing
[0092] The MOF-loaded red phosphorus lithium ion capacitor negative electrode material prepared in each experimental example is applied to a button-type lithium ion half-cell. The preparation method of the button-type lithium ion half-cell is as follows:
[0093] The MOF-loaded red phosphorus lithium ion capacitor negative electrode material, acetylene black, and binder polyvinylidene fluoride are ground in a mass ratio of 7:2:1, and the solvent N-methylpyrrolidone is added to grind evenly to obtain a battery slurry. The battery slurry is evenly scraped on a copper foil by a casting method, dried in a vacuum oven at 60°C for 24 hours, compacted, and punched into a disc with a diameter of 11 mm to serve as the negative electrode material of a lithium ion battery; a lithium sheet is used as a counter electrode, and a Waterman glass fiber is used as a diaphragm; the electrolyte includes 1M LiPF6 as an electrolyte, DEC, DMC, and EC as electrolytes in a volume ratio of 1:2:2, and FEC is added in a volume ratio of 10%; the assembly is carried out in an inert atmosphere glove box to obtain a button-type lithium ion half-cell.
[0094] Perform the following test:
[0095] Test 1: The button-type lithium-ion half-cell was subjected to constant current charge and discharge test at a voltage range of 0.01-3V and a current density of 0.1A / g-5A / g;
[0096] Test 2: The button-type lithium-ion half-cell was charged and discharged at a current density of 10 A / g.
[0097] The test results of the button-type lithium-ion half-cell assembled with the MOF-loaded red phosphorus lithium-ion capacitor negative electrode material based on the above embodiment are as follows: Figure 3-Figure 9 shown.
[0098] Figure 1 and Figure 2 1 and 3 are SEM images obtained by SEM testing. Figure 1 For Example 1, the MOF precursor synthesized by dimethylimidazole and zinc nitrate hexahydrate supports red phosphorus negative electrode material in a polyhedral shape with a size of about 500 nm. Figure 2 For Example 3, the MOF precursor synthesized by terephthalic acid and hydrated zinc nitrate loaded red phosphorus negative electrode material is in block shape with a size of more than 4 μm.
[0099] Figure 3 This is the electrochemical test of Example 3. Figure 3 This is the charge-discharge curve of Example 3 after 3 cycles, indicating that red phosphorus is loaded on the MOF precursor.
[0100] Figure 4 It is a comparative test diagram of Example 1 and Example 3, which shows that compared with the dimethylimidazole ligand, the longer ligand terephthalic acid can load more red phosphorus and exert a higher capacity.
[0101] Figure 5 It is a comparison chart of the specific capacity tests of Examples 2 to 4, which shows that using different heat treatment temperatures will affect the electrochemical performance of the MOF-loaded red phosphorus negative electrode material.
[0102] Figure 6 The figure is a comparative test result of the specific capacity of Example 3, Example 5 and Example 6. It shows that under argon atmosphere, the MOF precursor synthesized by terephthalic acid and hydrated zinc nitrate has the best rate performance of red phosphorus negative electrode material, with a specific capacity of more than 900 mAh / g at a low current density and more than 400 mAh / g at a high current density of 8A / g. Moreover, after 3000 cycles of charge and discharge with a high current, the capacity retention rate is above 75% ( Figure 8 ).
[0103] Figure 7These are the electrochemical test diagrams of Example 3, Example 7 and Example 8. It can be seen that the increase in the mass ratio of MOF precursor to red phosphorus does not improve the rate performance. Compared with Examples 7 and 8, the appropriate MOF precursor mass is sufficient to load red phosphorus, and more MOF precursor will affect the performance of red phosphorus.
[0104] Figure 8 In Example 3, the retention rate still reaches more than 75% after 3000 cycles of charge and discharge at a large current of 10 A / g, indicating that the MOF structure alleviates the problem of rapid capacity loss of red phosphorus due to volume expansion and material crushing during the charge and discharge process.
[0105] Fig. 9 This is the rate test diagram of Example 12. Compared with Examples 1 and 3, its performance decays faster. At a current density of 0.1 A / g, the maximum specific capacity is only 500-600 mAh / g, which is much lower than that of Examples 1 and 3. Moreover, at a high current density (10 A / g), the specific capacity is below 100 mA / g, and the performance is poor. MOF cannot load enough red phosphorus to exert its performance.
[0106] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0107] The parts not described in detail in the present description belong to the known technology in the art. The above embodiments are provided only for the purpose of describing the present invention, and are not intended to limit the scope of the present invention. The scope of the present invention is defined by the appended claims. Various equivalent substitutions and modifications made without departing from the spirit and principle of the present invention should be included within the scope of the present invention.
Claims
1. A MOF-loaded red phosphorus lithium ion capacitor negative electrode material, characterized in that: It comprises MOF and red phosphorus loaded in the pores of MOF; wherein the loading rate of red phosphorus on the MOF is 15-25%.
2. The MOF-loaded red phosphorus lithium ion capacitor negative electrode material according to claim 1, characterized in that: The MOFs are cubic particles on the micro or nano scale.
3. The method for preparing the MOF-loaded red phosphorus lithium ion capacitor negative electrode material according to claim 1 or 2, characterized in that: The following steps are involved: (1) Mix the MOF precursor and red phosphorus and place them in a sealed container; (2) heating the sealed container, performing heat treatment under vacuum or inert atmosphere, and obtaining the MOF-loaded red phosphorus lithium ion capacitor negative electrode material after cooling.
4. The preparation method according to claim 3, characterized in that: The weight ratio of the MOF precursor to red phosphorus is (1-3):
1.
5. The preparation method according to claim 3, characterized in that: The heat treatment process is: heating to 600-800°C at a heating rate of 3-5°C / min and keeping the temperature for 2-5h.
6. The preparation method according to claim 5, characterized in that: The heat treatment process also includes cooling the temperature to 300° C. at a cooling rate of 2-5° C. / min and keeping the temperature for 10-14 hours.
7. The preparation method according to claim 3, characterized in that: The inert gas is argon.
8. The preparation method according to claim 3, characterized in that: The MOF precursor is prepared by the following steps: Add the organic ligand to 20-100 ml of methanol to disperse it in the methanol; Add the hydrated metal salt to 20-100 ml of methanol to disperse it in the methanol; The two solutions are mixed, heated to 100-150°C, and stirred for 24-48 hours to allow for a full reaction; The obtained solution is centrifuged, washed, and vacuum dried to obtain a MOF precursor; Wherein, the mass ratio of the organic ligand to the hydrated metal salt is 1:(2-3).
9. The preparation method according to claim 1, characterized in that: The organic ligand is one of dimethylimidazole and terephthalic acid; the hydrated metal salt is zinc acetate hexahydrate or zinc nitrate hexahydrate.
10. A lithium ion capacitor, characterized in that: It comprises the MOF-loaded red phosphorus lithium ion capacitor negative electrode material as described in claim 1 or 2.